PIM Gender Research in 2016: Review - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2017)
While there is significant and promising gender research being done within PIM, there are considerable opportunities to strengthen existing gender research as well as incorporate gender analysis into activities and research areas that do not currently do so. This Review analyzes gender research and analysis conducted through PIM in 2016. The objectives are both to highlight examples of strong gender research and to identify the gaps. Not all papers can or should have a gender focus, but for research that has scope to include gender analysis, we have tried to highlight some opportunities.